Practices of oral health maintenance, caries protective factors and caries experience in adults in Sekeloa Region - Susilo, Fania Syakira; Aripin, Dudi; Suwargiani, Anne Agustina (Universitas Padjadjaran, 2021)
ABSTRACTIntroduction: Dental caries is still the most common oral disease experienced in Indonesia. Caries is caused by various factors. Practices in maintaining proper oral health are urgently needed to maintain healthy teeth and mouth to avoid various diseases, including caries. Caries prevention is inseparable from the role of protective factors that maintain the caries balance. This study was aimed at discovering the level of oral health maintenance practices, caries protective factors, as well as caries experience in adults in Sekeloa Region. Methods: The research method was descriptive cross-sectional with purposive sampling technique. The sample consisted of 61 permanent residents aged 35-44 years in South Sekeloa. Data was collected through questionnaire and DMF-T index examination. The questionnaire consisted of questions asking about respondent’s biodata, practices of oral health maintenance and caries protective factors. Questions of the questionnaire used in this study were adapted from several journals published by Cheng, Rahman, and Punitha13-15, then translated back and forth by the oathed translator and has been tested for validity and reliability using rank Spearman correlation. Analysis data using distribution frequency and categories using normal distribution curve. Results: This study shows that subjects performed good practices of oral health maintenance (47.54%), adequate (50.82%), bad (1.64%), and good caries protective factors (1.64%), adequate (52.46%), bad (45.90%). The caries experience degree reached 9.13 and was categorized as moderate. Conclusion: The oral health maintenance practices and caries protective factors in adults aged 35-44 years were adequate, and the degree of caries experience was moderate.